Determination of Involvement and Life Satisfaction Levels for Recreational Activities of Individuals who are Members of Fitness Centers - Koç, Mustafa Can; Yüzgenç, Ayşe Asli (Lahore Medical and Dental College, 2021)
Background: It can be thought that it is possible to define an individual's motivation and interest in a product or activity, the excitement of doing that job, as the concept of involvement. Aim: The aim of this research is to determine the involvement and life satisfaction levels for the recreational activities of individuals who are members of fitness centers. Methods: As a data collection tool in the research, Leisure Time Involvement Scale (LIS) developed by Kyle et al. (2007), whose validity and reliability for Turkish culture was made by Gürbüz et al. (2015), and Life Satisfaction Scale (LSS) developed by Diener et al., (1985) and adapted to Turkish culture by Köker (1991) were used. The population of the research consisted of private sports and fitness center users in Kastamonu, Samsun and Hatay provinces. The sample of the study consisted of 450 people (55% Female, 45% Male) who are members of private sports and fitness centers in Kastamonu, Samsun and Hatay provinces and were selected by purposive sampling method. Descriptive statistical methods (percentage, frequency, mean, standard deviation), T test, one-way analysis of variance ANOVA and pearson correlation test were used to analyze the data in the study. Results: According to the findings of the study, while there was a significant difference in the variables of age group, education level, frequency of use of the sports center, and hours spent daily in the sports center in the leisure time involvement scale, no significant difference was found in the gender variable. In the life satisfaction scale, while there was a significant difference in the variables of gender, education and weekly usage frequency, no significant difference was found in the age group and the daily hours spent in the sports center. Conclusion: In conclusion, the attractiveness factor has the strongest effect on individuals' leisure time involvement. In addition, it was determined that the participants' life satisfaction was high and there was a low and positive relationship between life satisfaction and leisure time involvement. Keywords: Fitness centers, Recreational activity, Involvement, Life satisfaction.